DAMPAK ADAPTASI PRESENTASI TREE-VIEW TERHADAP NIAT UNTUK MELAKUKAN PEMBELIAN SECARA ONLINE: EMOSI DAN SIKAP PENGGUNA SEBAGAI MEDIATOR (DIDASARKAN PADA STIMULUS-ORGANISM-RESPONSE MODEL) - Hidayatulloh, Amir (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
The purpose of this reserach is to fi nd out whether a method of adaptionpresentation tree-view has an impact on individual intention to purchase in online storewhich mediated by emotion and attitude toward the website. Sample was collected byusing purposive sampling method with criterias, such as a person who is ever browsingin online store and at least has two times online purchasing history. Data was collectedby using survey both distributed to responden directly as well as through internet, and220 sample done by testing. Statistical test was done using WarpPLS 3.0. The resultis user emotion increases when website use tree-view , whereas attitude toward thewebsite donât increase when website use tree-view. User emotion at browsing activityin website use tree-view adaptation and positive attitude of user on the website, fi nallyencourage individual to have purchase intention.